DINAMIKA PROFESI GURU: CITRA, HARAPAN, DAN TANTANGAN - Suraji, Imam (Jurnal Cakrawala Pendidikan, 2016)
Teacher is one of the major key holder in the success of education.process and study in school. Teachermust beresponsible professionally to parents, society, and nation. That is so strategic that the role of teacher for nation future, teacher should not be as a· secondary profession, but as first profession that it’s just believed to them who can fulfill the needed requirement. In daily life, teacher is expected to be able to be the function as a model for society (digugu Zan ditiru). That expectation is a challenge for teacher. To be able to fulfill· that· expectation, teacher must have teacher profession competence. Teacher must be expert on his major, understanding the science of·education, having good characteristic, attitude, and behavior, and also good in communicating with alldirections related with their job. Other requirement that is not less important is to believe, and God fearing, and also be· able to practice all thatare taught in daily life.